Vegetation response to the "African Humid Period" termination in Central Cameroon (7° N) – new pollen insight from Lake Mbalang - M. Servant (Climate of the Past, 2010)
A new pollen sequence from the Lake Mbalang (7°19´ N, 13°44´ E, 1110 m a.s.l.) located on the eastern Adamawa plateau, in Central Cameroon, is presented in this paper to analyze the Holocene African Humid Period (AHP) termination and related vegetation changes at 7° N in tropical Africa, completing an important transect for exploring shifts in the northern margin of the African Monsoon. This sequence, spanning the last 7000 cal yr BP, shows that the vegetation response to this transitional climatic period was marked by significant successional changes within the broad context of long-term aridification. Semi-deciduous/sub-montane forest retreat in this area is initially registered as early as ca. 6100 cal yr BP and modern savannah was definitely established at ca. 3000 cal yr BP and stabilized at ca. 2400 cal yr BP; but a slight forest regeneration episode is observed between ca. 5200 and ca. 4200 cal yr BP. In this area with modern high rainfall, increasing in the length of the dry season during the AHP termination linked to a contraction of the northern margin of the Intertropical Convergence Zone (ITCZ) from ca. 6100 cal yr BP onward, probably associated with decreasing in cloud cover and/or fog frequency, has primarily controlled vegetation dynamics and above all the disappearance of the forested environment on the Adamawa plateau. Compared to previous studies undertaken in northern tropical and Central Africa, this work clearly shows that the response of vegetation to transitional periods between climatic extremes such as the AHP termination might be different in timing, mode and amplitude according to the regional climate of the study sites, but also according to the stability of vegetation before and during these climatic transitions.